Relationships, oppression and resolutions: An editorial comment to the 45.3 issue of the Interamerican Journal of Psychology - Torres-Rivera, Edil (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2013)
An editorial comment to the 45.3 issue of the IJP.